(untitled) (Journal of Philosophy, Culture and Political Science, 2025)
The development of local self-government is essential for fostering citizen participation in addressing regional issues, enhancing civic engagement, deepening democracy within the political system, and increasing citizens’ understanding of the decision-making process at the state level. In Kazakhstan, several significant decisions have been made in recent years, including the introduction of a fourth level of the budget and the direct election of aul akims (mayors of villages, towns, and cities that are subordinate to districts) by residents. These initiatives aim to strengthen local self-government. The reforms implemented have stimulated scientific research to assess the effectiveness of public policy in this area. This study evaluates recent publications on local self-government in Kazakhstan through literature reviews. Consequently, the authors present several conclusions and recommendations for broader discussion. These recommendations are beneficial not only for evaluating recent government reforms but also for outlining future directions for policymakers and potential research avenues for academics. Keywords: local self-government, local government, aul akim